Innate immune imprints shape HIV-1 reservoir cell persistence during long-term antiretroviral therapy - Toong Seng Tan; WeiWei Sun; Ce Gao; Mathias Viard; Lucy C. Walters; Melanie Lancien; Yuko Yuki; Tram N. Van; Carlos Casquero; Xuan Guo; Rebecca Hoh; David W. Haas; et al. (Nature Immunology, 2026)
Abstract Host immune responses that can target and eliminate HIV-1 reservoir cells during suppressive antiretroviral therapy are poorly understood. Here, analyzing over 6,000 proviral DNA amplicons from 104 individuals on long-term antiretroviral therapy, we found that carriers of HLA-C2 allotypes, which promote NK cell education via interactions with KIR2DL1, exhibited lower frequencies of intact proviruses. No protective effects of HLA-C2 alleles were observed during untreated infection, suggesting a selective vulnerability of reservoir cells to NK-cell-mediated immune activity under antiretroviral therapy. Supporting this, frequencies of KIR2DL1 + NK cells, particularly those coexpressing the activating HLA-E receptor NKG2C, were inversely correlated with frequencies of intact proviruses. Moreover, viral protein U variants that strongly downregulate HLA-C, increasing a missing-self response by KIR2DL1 + NK cells, were associated with smaller reservoirs in carriers of HLA-C2. Infected cells surviving long-term displayed elevated HLA-C expression, consistent with in vivo selection for resistance to KIR2DL1 + NK-cell-mediated immune clearance. Immune activity of KIR2DL1 + NK cells against viral reservoir cells was enhanced by NKG2C–HLA-E interactions, as sequence variants in HLA-E-restricted HIV-1 epitopes reduced NKG2C-dependent NK cell activation and were associated with higher frequencies of intact proviruses. These findings underscore the critical influence of host and viral genetic variation on reservoir persistence and highlight opportunities for leveraging innate immunity in HIV cure strategies.